2019
DOI: 10.1186/s12862-019-1527-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative myoanatomy of Tardigrada: new insights from the heterotardigrades Actinarctus doryphorus (Tanarctidae) and Echiniscoides sigismundi (Echiniscoididae)

Abstract: BackgroundTardigrada is a group of microscopic invertebrates distributed worldwide in permanent and temporal aquatic habitats. Famous for their extreme stress tolerance, tardigrades are also of interest due to their close relationship with Arthropoda and Cycloneuralia. Despite recent efforts in analyzing the musculature of a number of tardigrade species, data on the class Heterotardigrada remain scarce. Aiming to expand the current morphological framework, and to promote the use of muscular body plans in eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Tardigrades survive extreme conditions by entering cryptobiosis -a state of extreme dormancy, where metabolism comes to a reversible stop. Cryptobiotic survival in turn depends on the organism sustaining structural integrity and our investigations indicate that actin filaments are crucial for stabilizing the three-dimensional structure of the anhydrobiotic state 22,25,61 . In effect, we propose that ATP dependent "rigor mortis" ensure tardigrade structure during anhydrobiosis.…”
Section: Discussionmentioning
confidence: 81%
“…Tardigrades survive extreme conditions by entering cryptobiosis -a state of extreme dormancy, where metabolism comes to a reversible stop. Cryptobiotic survival in turn depends on the organism sustaining structural integrity and our investigations indicate that actin filaments are crucial for stabilizing the three-dimensional structure of the anhydrobiotic state 22,25,61 . In effect, we propose that ATP dependent "rigor mortis" ensure tardigrade structure during anhydrobiosis.…”
Section: Discussionmentioning
confidence: 81%
“…diagonal ones in platyhelminthes [ 32 ]. There may be exceptions to this generalization; for example, nematodes [ 33 ], nematomorphs [ 34 ], tardigrades [ 35 , 36 ], arthropods [ 2 , 37 ] and some polychaete annelids [ 38 ] lack body-wall circular muscles, most likely due to secondary loss. The Early Cambrian lobopodian Tritonychus has an outer layer of longitudinal, a middle layer of oblique and an inner layer of circular muscles [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by the description of and current research on the Roscoff worm, Symsagittifera roscoffensis (Graff, 1891) (see e.g. [1,2]) and by investigations into the diversity and adaptations of tardigrades [3][4][5][6][7]. Notably, the phylum Loricifera was described in 1983 from the study of the first representative specimens found off the coast of Roscoff [8].…”
Section: Introductionmentioning
confidence: 99%